Screening and Etiology of Congenital Heart Disease in Developing Countries : A Comprehensive Systematic Review - Dzakiyyah Fiddin; Dhanista Hastinata Sukarna Putra; Irkhamyudhi Primasakti (International Medical Journal Corp. Ltd, 2025)
Introduction: The increasing number of newborns with congenital heart disease (CHD) shows that the global burden of CHD is still significant. This indicates that screening and prevention have not been carried out optimally. This study aims to determine the differences of screening and etiology of congenital heart disease (CHD) between developed and developing countries. Methods: A systematic review adhering to PRISMA 2020 guidelines was conducted. Studies from 2015 to 2025 focusing on the screening and etiology of CHD in developing and developed countries were included. Results: Twenty-three relevant studies were included. Combination of pulse oximetry (PO) and auscultation, or PO alone were the most common postnatal screening tools in developed and developing countries. For prenatal screening, ultrasound was commonly used. Artificial intelligence and genetic testing were only used in developed countries. The etiology such as genetics, maternal lifestyle or conditions were discussed. Conclusion: The urgent need for affordable early detection of congenital heart disease (CHD) in developing countries cannot be overstated, as it holds the potential to significantly reduce the global burden of this condition. By implementing comprehensive prenatal and postnatal screening programs, we can identify at-risk infants early, enabling timely interventions and improved health outcomes. Addressing this critical issue not only enhances individual lives but also strengthens healthcare systems and fosters healthier communities.